Pendampingan Digital Branding Melalui Reaktivasi Lokasi Google Maps Berstatus Tutup Permanen : Abdimas UD. Pia Toulip Digital Branding Assistance Through Reactivation of Google Maps Locations with Permanently Closed Status : Service to Society UD. Pia Tou - Lorine Tantalu; Sri Handayani; Wildan Eka Prasetya; Sudirman Sudirman (Universitas Tribhuwana Tunggadewi Malang, 2026)
UD. Pia Toulip is an MSME producing various traditional snacks in Malang Regency that has been operating for over ten decades. Due to the impact of the Covid-19 pandemic, business activities declined, leading to the loss of the owner's digital account credentials and causing the Google Maps profile to automatically change to